Pengaruh Pemberian Infusa Daun Tambora (Ageratum Conyzoides L) Terhadap Kualitas Karkas Ayam Broiler - Rudi Rudi; Surya Nur Rahmatullah (Universitas Mulawarman, 2021)
ABSTRACT This research was conducted in November - December 2019 for 35 days at the poultry farm on the Ir. H. Nusyirwan Ismail street in Samarinda City, this resreach using 100 broilers from PT Japfa Comfeed Indonesia strain of MB 202 which were divided into 25 heads.research design used a completely randomized design (CRD). The percentage of carcass and the percentage of abdominal fat were analyzed using ANOVA (Analysis of Variance). Total bacteria and fat content were analyzed descriptively. During the research the chickens were given 5 drinking water treatments and 5 replications, namely, P0 (control), P1 (20 ml/Liter), P2 (40 ml/Liter), P3 (60 ml/Liter), P4 (80 ml/Liter).The results showed that giving Tambora leaf infusion in drinking water to carcass percentage ranged from 63.38% - 74.81%, percentage of abdominal fat 0.85% - 1.62%, total bacteria 0 x 105CFU / g - 3 x 105CFU / g and meat fat content from 2.66% - 9.43%. Tambora leaf infusion in drinking water to the percentage of carcass and the percentage of abdominal fat did not have a significant effect (P> 0.05), the application of Tambora leaf infusion in drinking water to the total bacteria in chicken intestines did not exceed the threshold for microbial contamination based on the Indonesian National Standard ( SNI) No. 7388-2009. The application of Tambora leaf infusion in drinking water decreased the fat content of the meat. Key words: Tambora leaf, infusion, carcass, broiler chicken